UPAYA PENINGKATAN KINERJA KARYAWAN MELALUI REWARDS DI SHAFIRA CORPORARTION - Ansori, Ansori; Meinawati, Krisda Lakrisida (IKIP SILIWANGI, 2020)
This research is motivated by a problem found in Shafira Corporation namely a lack of employee discipline. While the lack of employee discipline, resulting in diminishing performance. This study aims to describe: (1) To find out management strategies in improving employee performance; (2) To find out the management process in managing employee performance; (3) To find out employee responses to management. This research is a qualitative descriptive study. The subject of this research is a management and all employees at PT Shafira Corporation. Data collection is done using survey methods. The techniques used in data analysis are data display, reduction, and conclusion drawing. The results showed that: (1) The results of the implementation of employee performance improvement programs were employees having the motivation to work harder and be more disciplined; (2) Efforts made by the implementation of programs to improve employee performance.Â